FRI0153 Role of ror gamma t inhibition in the il-23 minicircle model and spa patient tissue cultures. (12th June 2018) - Hoyt, K.; Galdamez, J.; Panzenbeck, M.; Souza, D.; Glynn, E.; Pelletier, J.; Lewis, M.; Nabozny, G.; Purdue, E.; Mandl, L.A.; Wahle, J.
Abstract : Background: Retinoic acid receptor related Orphan Receptor gamma t (RORγt) is a nuclear hormone receptor expressed in a subset of pathogenic T cells and innate lymphoid cells. RORγt regulates the transcription of key pro inflammatory cytokines such as IL-17 and IL-22 in response to multiple activation signals including cytokines and T cell receptor engagement. Antagonism of RORγt is hypothesised to block transcription of these pathogenic cytokines resulting in reduced tissue inflammation and aberrant joint remodelling. Spondyloarthropathy (SpA) is characterised by a peripheral oligoarthritis and enthesitis. A key feature of SpA is the imbalance between bone resorption and formation leading to aberrant bone formation and ankylosis. The contribution of the IL-23/IL-17 axis to the pathogenesis of SpA is supported by several lines of evidence. However, the specific role of RORγt in regulating the cellular and molecular pathways contributing to entheseal and synovial inflammation remains incompletely understood. Objectives: The goal of this study was to determine the role of RORγt antagonism in both an IL-23 minicircle in vivo model and ex vivo tissue culture model. Methods: Model 1: Mice were administered an IL-23 minicircle via hydrodynamic injection to induce systemic IL-23 expression on day 1. Starting on day 2, mice were dosed p.o. for 28 days. Mice were monitored daily for signs of arthritis. Upon sacrifice tissue was collected for mRNA biomarker analysis and histologic assessment. Model 2: Patients undergoing total hip replacement were recruited into 2 groups: SpA (either psoriatic arthritis or ankylosing spondylitis) or OA (osteoarthritis). Entheseal and synovial tissues were collected and cultured ±RORγt inhibitor and cytokine stimulation (hTNFa/hIL23) for 24 and 48 hours and then analysed for gene expression. Results: Model 1: Overexpression of IL-23 induced SpA like phenotype including enthesitis, synovitis and aberrant bone formation. RORγt inhibition resulted in significant reduction of inflammation and arthritic score, histologic parameters of bone remodelling, and tissue biomarkers associated with the IL-23 axis (IL17A, IL17F, IL22). Model 2: Both entheseal and synovial cultures from SpA patients expressed increased Th17 axis genes relative to OA after cultures. RORγt inhibition reduced the expression of these Th17 axis genes (IL17A, IL17F, IL22) as well as reducing tissue remodelling related genes (FN1, MMP1/3, BMP5), in alignment with the results seen in model 1. Conclusions: IL-23 induced Th17 axis gene expression induced a SpA- like phenotype in mice, -including arthritis and aberrant bone formation, that was reversed upon RORγt inhibition. Similarly, SpA patient explants showed increased expression of Th17 axis cytokines and tissue remodelling related genes that were decreased with RORγt inhibition. Together, these complementary approaches support the hypothesis that RORγt treatment could block inflammation as well the underlying pathologies associated with SpA. Disclosure of Interest: K. Hoyt Employee of: Boehringer Ingelheim, J. Galdamez: None declared, M. Panzenbeck Employee of: Boehringer Ingelheim, D. Souza Employee of: Boehringer Ingelheim, E. Glynn Employee of: Boehringer Ingelheim, J. Pelletier Employee of: Boehringer Ingelheim, M. Lewis Employee of: Boehringer Ingelheim, G. Nabozny Employee of: Boehringer Ingelheim, E. Purdue: None declared, L. Mandl Consultant for: Boehringer Ingelheim, J. Wahle Employee of: Boehringer Ingelheim